RGB led cube development - Dzulaikha Ramle (Nanyang Technological University, 2020)
Many research and implementations have been done in the recent years. This project will focus more on the development of the 8x8x8 RGB LED cube. This report serves to provide a clear background and overall structure of the cube. In addition, further development is explored to maximize the cube’s functionality. Background research of the various hardware components and software are conducted in this project. The author mainly developed the LED cube in a way that it can be controlled using a PC’s keyboard. On top of that, specific functions and modified programs are elaborated. Its limitation and future implementations are further discussed.